2017
DOI: 10.1136/bmjopen-2016-013129
|View full text |Cite
|
Sign up to set email alerts
|

Developing a national dental education research strategy: priorities, barriers and enablers

Abstract: ObjectivesThis study aimed to identify national dental education research (DER) priorities for the next 3–5 years and to identify barriers and enablers to DER.SettingScotland.ParticipantsIn this two-stage online questionnaire study, we collected data with multiple dental professions (eg, dentistry, dental nursing and dental hygiene) and stakeholder groups (eg, learners, clinicians, educators, managers, researchers and academics). Eighty-five participants completed the Stage 1 qualitative questionnaire and 649 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 25 publications
3
17
2
Order By: Relevance
“…Unclear career development plans for both dental faculty and dental students after their participation in undergraduate research projects 8,9,16,17,21 Inadequate cross‐institutional collaborations in the implementation of a dental undergraduate research programme 8,18,22‐26 Limited reports of the implementation of a dental undergraduate research programme in the literature, especially long‐term overviews 12,16,17,27 …”
Section: Introductionmentioning
confidence: 99%
“…Unclear career development plans for both dental faculty and dental students after their participation in undergraduate research projects 8,9,16,17,21 Inadequate cross‐institutional collaborations in the implementation of a dental undergraduate research programme 8,18,22‐26 Limited reports of the implementation of a dental undergraduate research programme in the literature, especially long‐term overviews 12,16,17,27 …”
Section: Introductionmentioning
confidence: 99%
“…Although these approaches vary and different methods are used to obtain the necessary information in each approach, it is important that the methods should appropriately be selected. Shirinbak et al ,[ 5 ] Ajjawi et al ,[ 26 ] Bahadori et al ,[ 10 ] Kolahi et al ,[ 18 ] and Malekafzali et al [ 39 ] determined the research priorities of different fields and organizations through applying different methods. Considering the recommendations in recent studies for the use of hybrid approaches and the great use of them in recent years, in the current study also, a hybrid approach was used for needs assessment and prioritization of the required researches based on the studied dental hospital's vision and objectives.…”
Section: Discussionmentioning
confidence: 99%
“…What is important in the needs assessment process is the agreement of all stakeholders on the list of priorities which should ideally be provided with the participation of stakeholders and users such as decision-makers, policy-makers, and managers. [ 13 26 27 28 29 30 ] Choosing a suitable model can facilitate and increase the accuracy and credibility of the needs assessment process. This study aimed to identify and prioritize the required researches in the field of oral and dental health based on a goal- and health-oriented hybrid approach with the participation of all stakeholders in a dental hospital in Tehran, Iran, in 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Internationally, the increasingly strict standard on dentists not only require professional knowledge, but also the ability of problem-solving and self-directed learning, critical thinking, team performance and the willingness and ability to learn throughout life to ultimately become experts (2019). Rola et al identified the priority of national dental education research and the first three are role of assessments in identifying competence, undergraduate curriculum prepares for practice and promotion of teamwork within the dental team (Ajjawi et al, 2017). To meet these requirements, a variety of innovative teaching methods have been applied including TBL, problem-based learning (PBL), case-based learning and flipped classroom, etc.…”
Section: Strengths and Limitationsmentioning
confidence: 99%